The Role of the Salmonella spvB IncF Plasmid and Its Resident Entry Exclusion Gene traS on Plasmid Exclusion - Oluwadare, Mopelola; Lee, Margie D.; Grim, Christopher J.; Lipp, Erin K.; Cheng, Ying; Maurer, John J. (Frontiers in Microbiology, 2020)
Salmonella enterica cause significant illnesses worldwide. There has been a marked increase in resistance to fluoroquinolones and -lactams/cephalosporins, antibiotics commonly used to treat salmonellosis. However, S. enterica serovars vary in their resistance to these and other antibiotics. The systemic virulence of some Salmonella serovars is due to a low copy number, IncF plasmid (65kb - 100 kb) that contains the ADP-ribosylating toxin, SpvB. This virulence plasmid is present in only nine Salmonella serovars. It is possible that the spvB-virulence plasmid excludes other plasmids and may explain why antibiotic resistance is slow to develop in certain Salmonella serovars such as S. Enteritidis. The distribution of plasmid entry exclusion genes traS/traT and traY/excA are variable in Salmonella IncF and IncI plasmids, respectively and may account for differences in emergent antimicrobial resistance for some Salmonella serovars. The goal of this study is to determine the contribution of the Salmonella spvB-virulence plasmid in F-plasmid exclusion. From conjugation experiments, S. Typhimurium exhibited lower conjugation frequency with incFI and incFII plasmids when the spvB-virulence plasmid is present. Furthermore, introduction of cloned incFI traS into a “plasmidless” S. Typhimurium LT2 strain and Escherichia coli DH5 excluded incFI plasmid. However, deletion of the virulence plasmid traS did not affect plasmid exclusion significantly compared to a spvB control deletion. In addition, differences in F plasmid conjugation in natural Salmonella isolates did not correlate with IncF or SpvB-virulence plasmid genotype. There appear to be other plasmid or chromosomal genes at play in plasmid exclusion that may be responsible for the slow development of antibiotic resistance in certain serovars.